Integrating team and organizational identity: a systematic literature analysis - Alessandro Rovetta; Alessandro Bortolotti; Riccardo Palumbo (Frontiers in Organizational Psychology)
This systematic literature review explores the impact of team and organizational identification on various factors such as wellbeing, behaviors, trust level, Organizational Citizenship Behavior (OCB) and goal achievement. We use Social Identity Theory (SIT) to understand these dynamics. While strong organizational identification is generally linked to positive employee wellbeing, the presence of multiple groups within an organization (Nested Identifications or NID) can complicate matters. Over-identification with a specific team, as opposed to the organization as a whole, can lead to dysfunctional dynamics and reduce organizational effectiveness. The research provides insights into the factors that influence the alignment between team and organizational identification and its effects on employee behaviors. It calls for a more integrated understanding of the phenomenon, including which group categories to observe and which outcomes are most affected by different levels of identification. The primary focus of this work is the interaction between workgroups and the organization as a whole. The aim is to fill existing knowledge gaps, providing theoretical and practical insights to enhance wellbeing and effectiveness through targeted identification strategies at individual, team, and organizational levels. This systematic review seeks to guide future research toward a deeper understanding of identification dynamics within organizations, emphasizing a comprehensive approach that considers the impact of the most important levels of identification.